Lila - Robinson, Marilynne (Galaxia Gutenberg, 2015)
Lila, homeless and alone after years of roaming the countryside, steps inside a small-town Iowa church -- the only available shelter from the rain -- and ignites a romance and a debate that will reshape her life. She becomes the wife of a minister, John Ames, and begins a new existence while trying to make sense of the days of suffering that preceded her newfound security. Neglected as a toddler, Lila was rescued by Doll, a canny young drifter, and brought up by her in a hardscrabble childhood. Together they crafted a life on the run, living hand-to-mouth with nothing but their sisterly bond and a ragged blade to protect them. But despite bouts of petty violence and moments of desperation, their shared life is laced with moments of joy and love. When Lila arrives in Gilead, she struggles to harmonize the life of her makeshift family and their days of hardship with the gentle Christian worldview of her husband that paradoxically judges those she loves.